Towards a well-functioning stock market in context: Critically appreciating issues in interpreting efficient markets research and its regulatory implications - Jim Haslam; Jiao Ji; Hanwen Sun (Journal of Capital Markets Studies (JCMS), 2018)
Purpose - The purpose of this paper is to summarise and reflect upon key issues at the interface of prices, information and regulation with a focus upon the stock market in context. Reflecting upon academic research in the area of efficient markets, and regulatory policy, the concern is to discern issues in terms of policy and support for policy. What does the research imply for policy? Is it possible that the research, perhaps given its rhetoric, can be misinterpreted in relation to policy? The study is also concerned to develop avenues for future research based on these considerations. Design/methodology/approach - The paper is an analytical and critical review and writing. Findings - The reading of the research suggests a pragmatic regulatory policy that should be concerned to improve stock market functioning, including with respect to information, as well as the context of which this is part. At the same time, the literature may be read as promoting anti-regulatory policy. Practical implications - On the one hand, these are consistent with the pragmatic policy referred to above. On the other hand, further research is suggested to explore substantively the rhetoric of the research and its interpretation and to explore understandings of the research and its implications amongst key constituencies in practice. Originality/value - The concern is to bring key insights from the academic literature together with a view to promoting a pragmatic policy orientation, while cautioning in a critical perspective about how this academic literature and research might be interpreted from a policy perspective.
Keywords: 330; Pricing; Policy; Regulation; Information; Market; Stock